Communication technologies and internal communication in an organization during the Covid-19 pandemic - Smoląg, Klaudia; Ślusarczyk, Oliwia (Technologie komunikacyjne a komunikacja wewnętrzna w organizacji w czasie pandemii Covid-19, 2021)
During the Covid-19 pandemic, communication between employees was mostly carried out remotely and was carried out using solutions in the field of communication technologies. This dependence on the communication tools used often translated into the quality of the communication process and its effectiveness. In addition, significant differences between remote communication and internal communication generate problems and have a negative impact on the commitment and motivation of employees. The aim of this study is to present selected aspects related to the use of communication technologies in internal communication. The considerations are based on the literature on the subject and selected studies on remote work and internal communication during the Covid-19 pandemic. The conducted desk research analysis shows that companies implementing remote work should focus their activities not only on the implementation of communication technology solutions, but also on a change in the approach to creating the internal communication process. Our contribution to the discussion consists in pointing out that the process of internal communication requires a new approach to its creation.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 2 (60), s. 47-55
Keywords: communication technologies; internal communication; remote work; pandemia COVID-19; technologie komunikacyjne; komunikacja wewnętrzna; praca zdalna